New India Rehabilitation and Resettlement Policy, and Associated Legislative Measures Relating to Land Acquisition - Singh, Shekhar (Hydro Nepal: Journal of Water, Energy and Environment, 2009)
Hydro Nepal: Journal of Water, Energy and Environment Issue No. 3, January, 2008 Page 46-47